Strangers & pilgrims: female preaching in America, 1740-1845 - Brekus, Catherine A. (Gender and American culture, 1998)
Intro -- Contents -- Recovering the History of Female Preaching in America -- 1 Female Evangelism in the Eighteenth- Century Revivals -- 2 Female Religious Leadership in the Age of Revolution -- 3 Female Preaching in the Early Nineteenth Century -- 4 Conversion and the Call to Preach -- 5 Evangelical Women in the Pulpit -- 6 Female Peddlers of the Word -- 7 The Battle over Female Preaching -- 8 Female Preaching in the Millerite Movement -- Write the Vision -- Female Preachers and Exhorters in America, 1740Ð1845 -- Bibliography.